Mandibles with two joints evolved much earlier in the history of insects: dicondyly is a synapomorphy of bristletails, silverfish and winged insects. (15th October 2014) - BLANKE, ALEXANDER; MACHIDA, RYUICHIRO; SZUCSICH, NIKOLAUS URBAN; WILDE, FABIAN; MISOF, BERNHARD
Abstract The evolution of two‐jointed mandibles is considered to be a major step during the evolution of early insects enabling the exploration of new types of food. Two‐jointed – or dicondylic – mandibles are believed to be a groundplan characteristic for winged insects and silverfish. Jumping bristletails are thought to possess mandibles with one joint and are the sistergroup of winged insects + silverfish. However, our knowledge of the cephalic morphology of bristletails is limited to data from a few species and thus fragmentary. We investigated the cephalic morphology of both families of bristletails, Meinertellidae and Machilidae. We focused on skeletal elements and the musculature and compared them with the corresponding structures found in silverfish and winged insects. Bristletails show a previously unknown coupling structure between the maxillary palps and the mandibles and an additional anterior articulation of the mandibles in the region of the anterior tentorial pits. The articulation can be homologised with the anterior articulation in silverfish and winged insects. Together with a description of the functional morphology of the mandible system of bristletails and a discussion of the homology of mandibular articulations and related characters, we provide conclusive evidence that bristletails are, in fact, dicondylic insects.